Trust in the European Union in Challenging Times
XIII, 248 p. 10 illus.
Keywords: This is the first book in the Interdisciplinary European Studies collection. This volume provides an interdisciplinary perspective on trust in the EU from the vantage point of political science, law and economics. It applies insights from a number of different dimensions – political institutions, legal convergence in criminal and civil law, social trust, digitalization, the diffusion of political values and norms, monetary convergence and the legitimacy of political systems – to approach the highly complex issue of trust in the EU in a clear-sighted, relevant and insightful manner. Written by renowned experts in the field, the style is accessible and reader-friendly, yet concise, knowledgeable and thought-provoking. The individual chapters combine up-to-date research findings with reflections on on-going political debates and offer useful, concrete ideas on what steps the EU could take to address the challenge of trust. The book provides the reader with invaluable insights into how trust, or rather the lack of trust, poses a challenge to the future of the social, economic and political developments in the EU. It is a must-read for policy-makers, students and interested members of the public who feel concerned by the future of Europe.